Study of Deaths due to Hanging on Autopsied Cases at Mortuary Government Medical College Hospital Jammu – A Retrospective Study (Indian Journal of Forensic Medicine & Toxicology, 2023)
Background:Hanging is a form of asphyxia caused by external pressure on upper airwaysderived from a bandtightened by the gravitational weight of the body. It could by suicidal or homicidal.Method: 50 dead bodies (35 males and 15 females) aged between 20-70 years old who died due to hanging werestudied. The autopsies were carried out to rule out genderdifferences,pattern ofligature marks on neck, ligaturematerial used, fractures of hyoid bone or thyroid cartilage in the neck, significant findings in dissection of neckcaused by death due to hanging, differences between antemortemand postmortem hanging, associated injuriesin hanging etc.Results: 35 (70%) males, 15 (30%) females dead bodies due to hanging 19 (38%) were summer, 20 (40%) in rainy,11 (22%) in winter season, 14 (28%) outdoor, 36 (72%) were outdoor hanging deaths, 36 (72%) ligatures wereabove the thyroid cartilage, 9 (18%) at the level of cartilage, 5 (10%) below the level of thyroid cartilage. Thesignificant findings of neck dissection were 30 (60%) in the present study.Conclusion: The present study of deaths due to hanging will certainly help the medico-legal experts todifferentiate betweensuicidalandhomicidal hanging.
Keywords: Ligature, Strangulation, Asphyxia, Thyroid cartilage, Hyoid bone